Improving postpartum screening after diabetes in pregnancy: Results of a pilot study in remote Australia. (2nd October 2018) - Kirkham, Renae; MacKay, Diana; Barzi, Federica; Whitbread, Cherie; Kirkwood, Marie; Graham, Sian; Van Dokkum, Paula; McIntyre, H. David; Shaw, Jonathan E.; Brown, Alex; O'Dea, Kerin; Connors, Christine; et al.
Abstract : Background: The postpartum period is a critical time to improve health outcomes for Aboriginal women, particularly for those who have chronic conditions. Aims: To assess enhanced support methods (for women following diabetes in pregnancy (DIP)) to improve completion rates of recommended postpartum health checks. Materials and Methods: Fifty‐three Aboriginal women in the Northern Territory (NT) were contacted in the postpartum period to encourage medical check‐ups. Messages were delivered through phone (call or text messages) or other methods (Facebook or email). The primary outcome was postpartum blood glucose testing (oral glucose tolerance testing (OGTT), random or fasting glucose and HbA1c). Results: Establishing contact with women was difficult. Of 137 messages sent to 52 women, 22 responded (42%). Phone was the most common contact method with successful contact made from 16 of 119 (13%) attempts. Rates of postpartum OGTT completion were higher in the group successfully contacted (32% vs 7%). However, for any postpartum glucose testing (including OGTT and HbA1c) rates were 25 of 42 (60%) and neither success in making contact nor the contact method was associated with higher rates. Conclusions: The small sample size limits our conclusions; however, results highlight that engaging remote women postpartum is difficult. While rates of postpartum OGTT completion differed according to successful contacts, rates of any postpartum blood glucose testing did not. Further research is needed to explore feasible intervention methods to improve postpartum screening after a pregnancy complicated by diabetes.